Effects of a program to strengthen general practice care on hospitalisation rates: a comparative observational study - Wensing, Michel; Szecsenyi, Joachim; Stock, Christian; Laux, Gunter (Scandinavian journal of primary health care, 2018)
Objective: To determine the effect of a large-scale program to strengthen general practice on hospitalisation rates.Methods: This observational study compared enrolled patients in the program and a sample of non-participating patients from non-participating GPs in the same geographic area in Germany. Key components of the program are: prompt access to care, comprehensiveness, continuity, empanelment, data-driven quality improvement, computerized decision support, and additional reimbursement of general practices. The outcomes in this study were hospitalisation, rehospitalisation, and avoidable hospital admission up to four years after patient inclusion. Poisson regression models and generalized estimating equations were used to estimate intervention effects.Results: In the baseline year, 19.1% were hospitalised and 13.6% had a potentially avoidable hospitalisation, 14.5% were rehospitalised within 4 weeks. Across the four observed years, yearly hospitalisations were 9.8 to 14.9% lower in enrolled patients, yearly re-hospitalisations were 5.3 to 11.5% lower, and yearly avoidable hospitalisations were 6.8 to 8.6% lower compared to the control cohort (all differences were statistically significant). The trend in the between-group difference for hospitalisations and re-hospitalisations increased, while it remained stable for avoidable hospitalisations.Conclusion: This study provides strong indications for the positive impact of strong general practice care on population outcomes.Key pointsA program to strengthen general practice in Germany comprised of prompt access to care, comprehensiveness, continuity, empanelment, data-driven quality improvement, computerized decision support, and additional reimbursement of general practices.Patients who remained in the program during 4 years had increasingly lowered rates of hospitalisation and rehospitalisation compared to a control group of patients.Avoidable hospitalisations were also lower, but no trend of further lowering was found. This might suggest a ceiling effect to impact of strong general practice on hospitalisations.
Gesehen am 12.03.2020